Influence of Active Travel to School on the Blood Pressure of In-School Children and Adolescents in Benue North West Senatorial District of Benue State - Ihuma, James; Chukwudo, Donatus Udochukwu; Asogwa, Louisa Nkemdilim; Kparev, Tavershima (International Journal of Human Kinetics, Health and Education, 2025)
This study examined the influence of active travel to school (ATS) on the blood pressure of in-school children and adolescents in Benue North West Senatorial District of Benue State. Ex-post facto design was adopted for the study. The study sample comprised 663 in-school children and adolescents, aged 10-18 years, who were recruited using a multi-stage sampling technique and evaluated. A self-structured questionnaire was used to obtain participants’ mode of travel. Subjects’ blood pressure was measured by auscultation method using a stethoscope and sphygmomanometer and in accordance with the protocol of the Fourth Report on the Diagnosis, Evaluation, and Treatment of High Blood Pressure in Children and Adolescents by the National High Blood Pressure Education Program Working Group on High Blood Pressure in Children and Adolescents. Analysis of variance (ANOVA) was used to test the hypotheses at 0.05 alpha level. The study demonstrated that ATS does not significantly influence systolic blood pressure (SBP) and diastolic blood pressure (DBP) (P= 0.05) respectively in children and adolescents in Benue North West Senatorial District of Benue State. It was therefore recommended that efforts to lower blood pressure in this population should not depend solely on advocating for ATS. Instead, a broader strategy such as taking a balanced diet, promoting games and sports beyond ATS, and having periodic health check-ups are necessary for public health.